Burden in the main caregiver - Fabiola Yonte Huete; Zahara Urién Pérez; Marta Martín Gutiérrez; María Remedios Montero Herrero (Fundación para el Desarrollo de la Enfermería, 2010)
Objectives: The main objective is to determine the degree of burden in the main caregivers of dependent patients, to analyse the profile of informal caregivers and dependent patients. Their claims and help received with caring, the influence of mental deteriorate and duration of care giving regarding the burden of caregivers.Methods: Descriptive cross-sectional observational study amongst 50 caregivers and dependents. We used descriptive statistics and correlational studies. Results: 86 % of caregivers were women, middle aged, son/daughter of the dependent, married, with basic studies, no work outside the home, the average time in the role of caregiver was 16,96 hours a day and 2,1 free hours a day. 64 % of them received family support and 68 % wish to receive economic aid. It was found that for 38 % of the caregivers there was no burden at all, 34 % of them had a minimum burden and 28 % a greater burden.Conclusion: There are some caregivers with moderate or great burden. Our caregiver wishes to receive economic help. Our research shows that the decrease of mental health and the years of evolution do not have a significant statistically influence on caregivers. It is necessary prioritize the interventions and its recipients, provide solutions for caregivers with a greater burden, trying to keep away "caregiver syndrome".